Healthcare Workers on the Frontlines of War: Essential Roles and Responsibilities - Yash Sailesh Kumar; Jasmine Shanthi Kamath (American Journal of Medicine Open, 2024)
This article explores the indispensable roles and responsibilities of healthcare workers on the frontlines of war, where they grapple with the profound challenges posed by conflict. In the midst of decimated healthcare infrastructure, these professionals become pivotal in delivering urgent medical care while facing significant risks. Beyond immediate healing, healthcare workers navigate the psychological toll of war, addressing widespread trauma and limited mental health support. They emerge as advocates for peace, documenting atrocities, and contribute to postwar recovery by rebuilding healthcare systems, providing psychosocial support, and participating in public health initiatives. This article illuminates the multifaceted impact of conflict on healthcare, underscoring the urgency for international cooperation and the safeguarding of healthcare workers in addressing the complex and pressing intersection of health and war.